A review of recent compound-specific isotope analysis studies applied to food authentication. (30th July 2023) - Liu, Hongyan; Nie, Jing; Liu, Yi; Wadood, Syed Abdul; Rogers, Karyne M.; Yuan, Yuwei; Gan, Ren-You
Graphical abstract: Highlights: δ 13 C was applied on food adulteration, geographical and organic authentication. The δ 15 N of amino acids and nitrate were effective on organic food authentication. The δ 2 H and δ 18 O of specific compounds usually link with the local water. CSIA could discriminate honey, beverage, essential oil and processed food effectively. Abstract: Compound-specific stable isotope analysis (CSIA) of food products is a relatively new and novel technique used to authenticate food and detect adulteration. This paper provides a review of recent on-line and off-line CSIA applications of plant and animal origin foods, essential oils and plant extracts. Different food discrimination techniques, applications, scope, and recent studies are discussed. CSIA δ 13 C values are widely used to verify geographical origin, organic production, and adulteration. The δ 15 N values of individual amino acids and nitrate fertilizers have proven effective to authenticate organic foods, while δ 2 H and δ 18 O values are useful to link food products with local precipitation for geographical origin verification. Most CSIA techniques focus on fatty acids, amino acids, monosaccharides, disaccharides, organic acids, and volatile compounds enabling more selective and detailed origin and authentication information than bulk isotope analyses.. In conclusion, CSIA has a stronger analytical advantage for the authentication of food compared to bulk stable isotope analysis, especially for honey, beverages, essential oils, and processed foods.